(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
The present study aims at accounting for the holistic marketing’s role in Its four dimensions (integrated marketing , internal marketing, relationship marketing and performance marketing) in the customer’s value, in its five dimensions:- quality , price, sentimental value, social value, reputation . The present study hypothesizes that the private universities concerned do not have the real understanding and comprehensive recognition as regards the two concepts of holistic marketing and customer’s value.The research variables have been chosen due to their newness and importance, besides their application in the Iraqi environment. Two hypotheses have been suggested in this study: - hypothesis one: there is no correlation of statistical value between holistic marketing and customer’s value; - hypothesis two: there is no effect relationship of statistical value between holistic marketing and customer’s value. The study was conducted in five private colleges: Al-Turath College, Al-Rafidain College, Al-Maamoun College, Al-Mansour College, and Baghdad College of Economic Sciences. The number of students in these colleges is 24,535 male and female students, and the research sample is (400) male and female students. Data were collected through a questionnaire and personal interviews. The statistical software used to analyze the collected data is SPSS-V.24. The main findings of the study are there is a positive correlation and effect relationship between holistic marketing and customer’s value; the variable most connected with the customer’s value is the performance marketing and the variable most effective for the customer’s value is integrated marketing. The study recommends that Private colleges under study should organize symposiums and workshops, give lectures, etc. to acquaint their employees and personnel with the importance of holistic marketing. These colleges should build in their personnel organizational knowledge of the philosophy of holistic marketing to make them adopt this concept in their daily dealings. The philosophy of the higher Administration and the philosophy of holistic marketing should go in coordination with each other. Due importance should be given to the customer’s value achieving a high level of this value is a guarantee to achieving the goals targeted by these colleges